Twin transformation as a strategic approach in sport management: the synergy of digitalization and sustainability in sports - Ekaterina Glebova; Ekaterina Glebova; Dag Øivind Madsen (Frontiers Media S.A., 2024)
The integration of digitalization and sustainability principles, encapsulated within the Twin Transformation (TT) approach, has emerged as a transformative paradigm within sport management. However, there is a critical gap in understanding how these two transformative forces can be synergistically harnessed within the field of sport management. This paper explores the conceptual underpinnings of TT and its implications for enhancing organizational performance and addressing contemporary challenges in the sports industry. Drawing upon interdisciplinary perspectives, the paper examines how TT fosters innovation, enhances fan engagement, and promotes environmental responsibility within sport management. Through a synthesis of theoretical insights and practical examples, the paper highlights the potential of TT to drive positive change across various facets of sport management, from operational practices to stakeholder engagement. Furthermore, the paper underscores the importance of ongoing research and scholarly inquiry in advancing our understanding of TT and its implications for theory and practice in sport management. Overall, this paper provides a comprehensive overview of TT in sport management, offering valuable insights for researchers, practitioners, and stakeholders seeking to navigate the dynamic landscape of the sports industry.